2010
DOI: 10.1007/s11010-010-0392-y
|View full text |Cite
|
Sign up to set email alerts
|

Proximity of Na+–Ca2+-exchanger and sarco/endoplasmic reticulum Ca2+ pump in pig coronary artery smooth muscle: fluorescence microscopy

Abstract: Pig coronary artery smooth muscle expresses the Na(+)-Ca(2+)-exchanger NCX1 and the sarco/endoplasmic reticulum (SER) Ca(2+) pump SERCA2. NCX has been proposed to play a role in refilling the SER Ca(2+) pool. Caveolae may also direct Ca(2+) traffic during cell signaling. Here, we use immunofluorescence microscopy to determine if there is proximity between NCX1, SERCA2, and the caveolar protein caveolin-1. Stacks of images of cell surface domains were analyzed. Image stacks for one protein were analyzed for ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Scale bars were inserted assuming 0.065 μm/pixel resolution. 26 Transmission Electron Microscopy (TEM). SG samples were prepared as described above in glass vials and aged with buffer for 24 and 48 h. After aging, the buffer was removed and the gels were submerged in 2.5% glutaraldehyde for at least 4 days at 4 °C.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scale bars were inserted assuming 0.065 μm/pixel resolution. 26 Transmission Electron Microscopy (TEM). SG samples were prepared as described above in glass vials and aged with buffer for 24 and 48 h. After aging, the buffer was removed and the gels were submerged in 2.5% glutaraldehyde for at least 4 days at 4 °C.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Images were cropped using ImageJ (NIH, USA). Scale bars were inserted assuming 0.065 μm/pixel resolution …”
Section: Methodsmentioning
confidence: 99%
“…For example, NCX is co-localized with the transient receptor potential-like channel 6 (TRPC6), a non-specific cation channel, through which the Na + influx and the elevated local Na + concentration can increase the reverse mode NCX activity, resulting in net Ca 2+ influx (Pulina et al, 2013). A further peculiarity of this pathway is the proximity of NCX and the sarco(endo)plasmic reticulum Ca 2+ -ATP-ase, that finally allows the Na + influx to regulate the SR Ca 2+ content (Kuszczak et al, 2010). Similar coupling has been described between NCX and the alpha2 isoform of the Na + -K + -ATP-ase (NKA) (Zhang et al, 2005) (Hauck andFrishman, 2012), which has been shown to participate in the regulation of vascular tone and development of hypertension induced by endogenous ouabain (Blaustein et al, 2012).…”
Section: Role Of Ncx In the Development Of Hypertensionmentioning
confidence: 99%
“…; Kuszczak et al . ). In cardiomyocytes, α2 pumps and NCX are found at, or adjacent to (Scriven et al .…”
Section: Introductionmentioning
confidence: 97%
“…There may, however, be some overlap with α1 in these microdomains (Mohler et al 2003;Dey et al 2012). Na + /Ca 2+ exchangers (NCX), too, are localized in the PM-jS/ER microdomains (Figs 1 and 2) (Juhaszova & Blaustein, 1997a;Berry et al 2007;Lynch et al 2008;Davis et al 2009;Jayasinghe et al 2009;Kuszczak et al 2010). In cardiomyocytes, α2 pumps and NCX are found at, or adjacent to (Scriven et al 2000), PM-S/ER junctions in the transverse (t-) tubules as well as in the surface membrane ( Fig.…”
Section: Introductionmentioning
confidence: 97%